MODULASI MIKROBIOTA USUS MELALUI FERMENTASI PANGAN LOKAL DALAM PENCEGAHAN SINDROM METABOLIK - Maulidya Machdaniar; Lintang Mega Pertiwi; Ibnu Gunawan (LPPM STIKes Mitra Adiguna, 2026)
Metabolic syndrome is a cluster of cardiometabolic risk factors with an increasing global prevalence, including in Indonesia (21.66%). Gut microbiota dysbiosis has been identified as a central mechanism linking dietary patterns to metabolic syndrome pathogenesis through inflammatory pathways, insulin resistance, and hepatic dysfunction. Fermented foods represent a promising non-pharmacological prevention strategy through modulation of the gut microbiota ecosystem; however, evidence based on Indonesian local foods remains scarce. This study employed a Systematic Literature Review (SLR) approach combined with bibliometric analysis using VOSviewer 1.6.20 on 106 selected articles from the ScienceDirect database (2016–2026). The analysis identified four major clusters: (1) gut microbiota composition modulation and lipid-hepatic regulation via the gut–liver axis; (2) microbiota–SCFA–insulin resistance interactions; (3) gene expression regulation and PI3K/AKT cellular signaling; and (4) translational applications of probiotic- and prebiotic-based functional foods. Cross-cluster synthesis revealed that short-chain fatty acids (SCFAs), particularly butyrate, serve as key mediators linking all four pathways simultaneously. Traditional Indonesian fermented foods such as tempe, oncom, and tape possess inherent synbiotic potential yet remain systematically unexplored. These findings underscore the urgency of conducting clinical research on local Indonesian fermented foods to support nutritional policy development and functional food innovation.